The effect of Pluchea Indica (L) (Beluntas) extracts on the insulin release of RIN5F cell line. - Kasmuri, Abdul Razak; Bakhtiar, M. Taher; Suriyah, Wastuti (2012)
Our previous study showed that crude extract of Pluchea Indica was able to lower blood glucose levels in hypoglycaemic test on normal rats. This study is an attempt to demonstrate whether the effect was directly related to the effect on the insulin release by the pancreatic B cell. The B cell line of RIN5f of rats insulinamo were used in studying the insulin-releasing effect of sequential extractions of Pluchea Indica. The solvents used in the extraction were in the sequence of hexane, dichloromethane, ethyl acetate and methanol. Beside the sequential extractions there was a water extract of the plant. An antidiabetic drug, glibenclamide, which is known to stimulate B cells to produce insulin, was used as the positive control. The results showed that glibenclamide-treated, hexane, dichloromethane and water extract-treated groups were significantly increased the insulin release (p<0.01 and p<0.05 for all extract-treated groups). Thus the study showed that the model was able to demonstrate the stimulating effect of glibenclamide and show the effect of the plant extracts on B cells.